THE EFFECT OF RUMEN UNDEGRADABLE PROTEIN LEVEL OF CONCENTRATE WITH RICE STRAW AS BASAL DIET ON GROWTH PERFORMANCE OF SUMBA ONGOLE BEEF CATTLE - Ainin Fauzyah; Panjono Panjono; Ali Agus; I Gede Suparta Budisatria; Budi Prasetyo Widyobroto (Buletin Peternakan, 2017)
This research was conducted to determine growth performance of SO beef catlle fed rice straw added with concentrate with different levels of RUP, RUP used was soybean meal protected with 0.8% formaldehyde. Thirty six SO bull were divided into two groups at random, group that fed low and high RUP. Feed in the form of rice straw and concentrate with a ratio of 30:70 in dry matter (DM). Cattle fed low RUP get concentrate containing DM 91.22%, crude protein (CP) 19.38%, RUP 33.05%, and TDN 51.71%, whereas cattle fed high RUP get a concentrate with DM 91.13%, CP 19.40%, RUP 41.13%, and TDN 51.57%. Water was given unlimited. The nutrient intake and growth performance parameters analyzed using independent sample t-test, average daily gain was analyzed by ANCOVA with initial body weight as covariates. Intake RDP and RUP had significant effect (P<0.05) between cattle fed low and high RUP. Nutrient intake (DM, CP, TDN) and growth performance (average daily gain (ADG), feed conversion, feed cost per gain) showed not significant between cattle fed low and high RUP. The conclusion were the increased of RUP levels could improved growth performance of SO beff cattle.